Option pricing with V. G. Martingale components - Frank Milne; Dilip Madan (Queen's University, Department of Economics, 2008)
European call options are priced when the uncertainty driving the stock price follows the V. G. stochastic process (Madan and Seneta 1990). The incomplete markets equilibrium change of measure is approximated and identified using the log return mean. variance, and kurtosis. An exact equilibrium interpretation is also provided, allowing inference about relative risk aversion coefficients from option prices. Relative to Black-Scholes, V. G. option values are higher, particularly so for out of the money options with long maturity on stocks with high means, low variances, and high kurtosis.
Keywords: 330; option pricing; martingales; V. G. process; Optionspreistheorie; Black-Scholes-Modell; EU-Staaten